Mono-, bis- e tris-triazenos, tetrazeno e complexos de Cu(I), Ag(I), Au(I), Cu(II), Ni(II), Pd(II) E Cu(III): síntese, caracterização, estrutura cristalina, atividades antitumoral, antibacteriana e de clivagem do DNA in vitro - Paraginski, Gustavo Luiz (2013)
Multi-nitrogenated ligands are versatile coordinating ligands to the transition metals. In this work, mono- and bis-triazenes, a tris-triazene, a tetrazenide and twelve metal complexes were synthesized, including the metal ions Cu(I), Ag(I), Au(I), Cu(II), Ni(II), Pd(II) and Cu(III). The triazenes and complexes were characterized by different analysis: infrared and UV-Vis spectroscopy, 1H, 13C and 31P NMR spectroscopy, low or high resolution mass spectrometry (EI, ESI, ESI(+)-TOF and ESI(-)-TOF) and X-ray diffraction on single crystal. The Cu(II) complex of the mono-triazenide N-oxide ligand [(2-Ph)ArNNN(®O)CH3]- (2) shows cis geometry on the coordinated center and possesses intramolecular Cu(II)···arene- interactions. Four complexes [(R’)ArNNNAr(R’’)Au(I)PPh3] were synthesized: 4 (R’ = OCH3, R’’ = 2-Ph), 6 (R’ = R’’ = 2-Ph), 8 (R’ = R’’ = 4-C(O)NH2) e 10 (R’ = 2-F, R’’ = 4-C(O)NH2). The crystal structure of 6 shows intramolecular Au(I)···arene- interaction. The complexes 8 and 10 are biologically active in vitro (antitumoral, antibacterial and DNA cleavage activities), showing better DNA cleavage in pH 6,5 at 50° C. These two complexes exhibit hydrogen bonding through the amide groups. The bis-triazenes [(R)ArNNN(H)(CH2)4N(H)NNAr(R)] 11 (R = H) and 15 (R = 2-C(O)NH2) are rotamers as showed in the 1H and 13C NMR spectra. The bis-triazene 11 shows interesting property in promoting the formation of binuclear complexes of Cu(II) (12), Ni(II) (13) and Pd(II) (14) with very short M−M distances and really strong M···M interactions. The Cu(II) complex (12) shows antiferromagnetism due to the strong Cu−Cu antiferromagnetic coupling. The three complexes (12, 13 and 14) exhibit intramolecular C−H···M anagostic interactions and intermolecular C−H···Ph interactions promoting supramolecular arrangement in the solid state. The copper tetrazenide complex 16 was synthesized from the reaction of the 2-amidephenylazide with Cu(OAc)2·H2O in EtOH in the presence of KOH and exemplifies a stable polimeric salt of potassium with the deprotonated amide group. A reaction mechanism of formation of the complex 16 is proposed. It is supposed , that the oxidation state of the Cu is +3, based on the square planar geometry of the copper, short Cu−N bond distances, different bond distances N−N in the tetrazenido chain (N−N=N−N), and diamagnetism. However, XANES and EXAFS should confirm it. The tripodal tris-triazene 17 is the first completely characterized of this class of molecule including the X-ray diffraction on single crystal analysis. Depending on the crystallization conditions, the crystal structures of 17 show a water or a DMSO molecule inside the cavity formed by the three triazene chains, depending on the crystallization conditions. The tristriazenide gives a trinuclear complex of Cu(II) (18) with two ligands double deprotonated. This complex is paramagnetic. The complexes 19 (M = Cu(I)) and 20 (M = Ag(I)) have similar structure to each other, being salts where the anionic part is composed by two ligands tris-triazenides completely deprotonated surrounding a cluster of the M5 type, while the cationic part is composed by the M+(PPh3)3OH2 fragment.